Perioperative Assessment of the Maxillofacial Surgery Patient Problem-based Patient Management (Springer International Publishing, 2018)
This book is designed to guide the practitioner in the medical and anesthetic management of the maxillofacial surgery patient, serving as a comprehensive, up-to-date resource that will assist in patient work-up and response to any medical problem. It is divided into four sections that provide an overview of general and basic topics relevant to perioperative assessment, explain the assessment and management of diverse medical issues and co-morbidities, discuss the perioperative, pharmacological, and supportive management of maxillofactial treatment, and identify potential complications and their management. All of the authors have been carefully selected for their expertise in the topics that they discuss. While the book will be especially valuable for oral and maxillofacial surgeons, it will also be highly relevant for multiple other health care providers, including dentists, dental specialists, dental hygienists, otolaryngologists, plastic and reconstructive surgeons, medical residents, nurses, and physician assistants.